Identifying listening and speaking difficulties: Bangladesh higher education students’ perspectives - Tanzila Shahid; Muhammad Kamarul Kabilan (Indonesian Journal of Applied Linguistics)
The importance of communication skills, particularly listening and speaking, is undeniable in today's world. However, studies have reported various difficulties with these skills in the context of higher education in Bangladesh, especially in the arts faculty. The underlying causes and challenges, particularly in higher education settings, remain under-researched. This study aims to address this gap by investigating the listening and speaking needs of higher education students in an arts faculty department. A case study approach was employed, utilizing open-ended items, in-depth interviews, diagnostic tests, and document analysis. The findings revealed that students face challenges in areas such as pronunciation, grammar, vocabulary, and fluency, with nervousness, lack of confidence, and hesitation acting as significant barriers to skill development. Furthermore, there was a clear imbalance between students' needs and the content of course syllabi and examination systems. The study suggests enhancing Hutchinson and Waters's (1987) learning needs approach to better align with national development policies in countries where English is a second or foreign language. These findings highlight the need for curriculum reforms and more targeted instructional strategies that address students' real-world listening and speaking needs, ultimately fostering more effective communication skills in higher education contexts.